Corporate sustainability : integrating performance and reporting - Brockett, Anne; Rezaee, Zabihollah , 1953- (The Wiley corporate F&A series, 2012)
Global businesses are under close scrutiny and profound pressure from lawmakers, regulators, the investment community, and their diverse stakeholders to focus on sustainability and accept accountability and responsibility for their multiple bottom lines of economic,governance, social, ethical, and environmental (EGSEE) performance. Would you like to leave more resources for the next generation? Watch your business grow continuously? Have an ethical and competent organizational culture? Presenting recent developments in sustainability performance and sustainability reporting and assurance, Corporate Sustainability sheds light on the importance, relevance, and benefits of business sustainability and accountability reporting in all areas of EGSEE performance. Filled with features and practical examples relevant to professionals of all levels, corporate leaders,directors and executives, as well as auditors, practitioners, and educators, this timely and essential book discusses: How organizations focused on sustainability performance and accountability reporting can reflect their key performance indicators (KPIs) in every area of EGSEE business affairs. The importance of sustainability performance, reporting, and assurance. The initiatives, rules, regulations, and standards of performance and reporting. Emerging issues and best practices of sustainability performance, reporting, and assurance. Future trends in sustainability performance Organizations worldwide recognize the importance of sustainability performance and accountability reporting. However, how to actually implement sustainability reporting remains a major challenge. Read Corporate Sustainability and discover how to fully--and successfully--integrate sustainability into your business's reporting and performance management systems